A Comparative Analysis of Kidney Donation Regulations and Ethics in Spain, the USA, and Iran: Lessons for The Indonesian - Netral Gulo; Yulia; Anggri Noorana Zahra; Agung Waluyo (Nursing Current: Jurnal Keperawatan, 2026)
Background: Inequity in kidney donor availability remains a global challenge, including in Indonesia. Comparative analyses of different regulatory models and their ethical implications for Indonesia are still limited. Objective: To compare kidney donation regulations and ethical frameworks in Spain (opt-out), the United States (opt-in), and Iran (regulated compensation), and assess their relevance for Indonesia. Methods: A narrative literature review with a comparative thematic analysis was conducted on 12 articles published between 2015 and 2025. Results: The effectiveness of kidney donation systems depends not only on legal frameworks but also on implementation, public trust, donor protection, and transparency. Spain achieved high participation through a coordinated opt-out system and strong public education. The United States emphasized autonomy through opt-in but faced challenges in equitable distribution. Iran increased donor availability via regulated compensation, though ethical concerns regarding potential exploitation remain.cConclusion: No single model is universally applicable. Indonesia requires a context-specific approach integrating ethical principles, sociocultural values, and institutional capacity, with emphasis on public education, transparency, and donor protection.